Persepsi Masyarakat Mengenai Pernikahan Siri Online - Muhammad Fadlu Rahman; Iwan Hermawan (Universitas Islam Madura, 2022)
The phenomenon of unregistered marriage on the internet is starting to get crowded at this time. The internet, which used to be a medium for obtaining information, has been misunderstood by irresponsible parties. Marriage is a very sacred thing for mankind, and also has a sacred purpose, not separated from religious rules. People who marry not only to satisfy their inner desires, but to achieve peace, tranquility, and mutual growth between husband and wife on the basis of deep love. In addition, on the basis of morality, the nuances of ukhuwah basyariyah and Islamiyah are combined to establish a brotherly relationship between the two families of the two partners. The method in this study is to adopt a qualitative method, the data obtained through interviews and observations, and the nature of the document, making the results obtained in this study appear in the form of a series of words instead of numbers. In addition, it uses descriptive techniques to analyze data, describes reality/events according to the results, and tends to use inductive analysis methods, namely using general things (conceptual level) starting from specific things (experience facts).